PENGGUNAAN METODE PEMBELAJARAN MULTIMEDIA BERBASIS OBJECT-ORIENTED PROGRAMMING (ADOBE-FLASH) PADA MATA PELAJARAN BAHASA INGGRIS - Resty Wahyuni (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
The aim of the research are (1) to know an influence on the development of Adobe-Flash multimedia programs on the ability of students to improve vocabulary skills in English. (2)  to find the percentage of the influence of the development of multimedia programs on the ability of students to improve vocabulary skills in English. This research is an experimental research. The program implementation technique for this research is a preliminary test used to measure students' vocabulary abilities of the material being taught while the final test is carried out to determine student learning outcomes after being treated using Multimedia-based Object-Oriented Programming (AdobeFlash) learning methods in English.  Keywords: Multimedia-Based Learning Method, Vocabulary Skills, English.